Effectiveness of Psilocybin on Depression: A Qualitative Study - Al-Naggar, RA; Alshaikhli, H; Erlam, G (Modestum, 2021)
Introduction: Psilocybin mushroom use is well documented in spiritual and religious ceremonies globally. This drug is now the most popular in Europe and the USA. Objective: The objective of this study is to explore the experiences and effects of psilocybin on patients with depression and anxiety. Method: A qualitative study was conducted interviewing ten participants currently taking psilocybin while experiencing depression and/or anxiety. Ethical approval was obtained from the University ethics committee. Participants were recruited via social media and groups are known to have used psilocybin for the treatment of anxiety and/or depression. Participants were informed of study aims and consent was obtained before interviews commenced. Confidentiality was maintained throughout this study. Interviews began with informing participants that psilocybin may be effective in the management of depression. Initially, information around the way treatment with psilocybin was obtained was sought. This was followed by queries around the effects of the drug in terms of experiences both during and after treatment. Finally, participants were asked to outline the positive effects of psilocybin on their lives. Results: The data were thematically coded using Grounded Theory as an underpinning philosophical paradigm. Emerging themes included enhancement of smell, vision, hearing, and taste sensations. Another theme emerging was the experience of being ‘connected with the universe’ while on the drug. Additionally, participants reported a stabilization of mood, an increase in optimism and emotional control, and a healthier emotional connection with others. Most also felt an increase in comfort, peace and calmness. Another theme that emerged centered on the mechanism of action of psilocybin. Participants stated that this substance seemed to ‘make new connections in their brain,’ resulting in new perspectives. Some participants felt this resulted in a calming influence on the mind and body. This aligns with research showing that psilocybin works by changing the thinking and improving information processing. Conclusion: Psilocybin has promising effects on the patients with depression/anxiety even after a single dose. Psilocybin is safe but the administration should be guided by a health professional to yield safe and positive outcomes.
Keywords: Psilocybin; Depression; Qualitative; Mushroom